Engineering properties of sustainable green concrete incorporating eco-friendly aggregate of crumb rubber: A review. (15th November 2021) - Qaidi, Shaker M.A.; Dinkha, Youkhanna Zayia; Haido, James H.; Ali, Msheer Hasan; Tayeh, Bassam A.
Abstract: The disposal of waste rubber tires has become a main ecological issue around the world. Each year, millions of tires are disposed of, buried, or thrown away, which is a severe hazard for the environment due to its prolonged degrading period. Therefore, recycling waste rubber as aggregates as a supplemental construction material is beneficial. The usage of crumbs rubber (CR) would be led to sustainable utilization of waste material, which would preserve depleting natural aggregate sources and protecting the environment. This paper reviews the published research on the performance of concrete containing CR as eco-friendly aggregates. Moreover, it highlights the impact in terms of aggregate substitution content, form, size, and waste treatment on the fresh and mechanical properties of crumb rubber concrete (CRC). The paper also aims to update the database for further experimental and numerical research on rubberized concrete.